2016
DOI: 10.1111/curt.12128
|View full text |Cite
|
Sign up to set email alerts
|

Citrus and Orangeries in Northern Europe

Abstract: Summary The genus Citrus comprises c. 25 species distributed from north‐east India and China to Australia and New Caledonia. Citrus fruits today make up the most significant component of fruit‐growing in warm countries, and extracts from them provide not only a very large share of the juice industry but are also used in many consumer products. When the first of them were brought to Europe, two millennia ago, however, they were not even consumed – the fruits being used for scenting and moth‐proofing clothes. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For the second out-of-season cropping cycle, two types of plant materials were utilized: (i) same 'old' plants that had already produced in the regular first cropping cycle (winter to spring), which after harvest were intensively pruned on 8 July to a single vigorous well lignified cane with 6-7 buds and (ii) cold stored (from March to July) dormant 'new' plants introduced into the greenhouse on the same date (8 July). Budbreak occurred in both cases just in about one week (15)(16)(17)(18). For both the cultivars, whereas the first cropping cycle had lasted on average about 128 days, the second cycle (summer-autumn) was completed in about 90 days due to the shorter duration of both the intervals budbreak to flowering and veraison to harvest (Table 3 and Figure 3).…”
Section: The Italian Research Activity On Tgscmentioning
confidence: 96%
See 1 more Smart Citation
“…For the second out-of-season cropping cycle, two types of plant materials were utilized: (i) same 'old' plants that had already produced in the regular first cropping cycle (winter to spring), which after harvest were intensively pruned on 8 July to a single vigorous well lignified cane with 6-7 buds and (ii) cold stored (from March to July) dormant 'new' plants introduced into the greenhouse on the same date (8 July). Budbreak occurred in both cases just in about one week (15)(16)(17)(18). For both the cultivars, whereas the first cropping cycle had lasted on average about 128 days, the second cycle (summer-autumn) was completed in about 90 days due to the shorter duration of both the intervals budbreak to flowering and veraison to harvest (Table 3 and Figure 3).…”
Section: The Italian Research Activity On Tgscmentioning
confidence: 96%
“…At the beginning of the last century an Italian agronomist reported that: 'the cultivation of vines in pots, as well as provide pleasure and satisfaction, may be advantageous because it often gives amazing results for quantity, quality, and beauty of the product' [15]. On the other hand, there is some historical evidence of ancient usage of container grown plants from the Egyptian age to the Renaissance age [16,17].…”
Section: The Rationale For the Soil-less Table-grape System Cultivati...mentioning
confidence: 99%
“…The writings indicate the use of Ondol, a traditional underfloor heating system, to grow mandarin (citrus) plants and ripen the fruit. In the 17th and 18th centuries, structures called Orangeries were used in France to protect fruit trees from cold temperatures (Wearn and Mabberley, 2016). These structures were tall masonry buildings with large glass windows on the southern side to allow sunlight.…”
Section: The Beginningmentioning
confidence: 99%
“…This type of container-growing, with a preference for the strangest and most "bizarre" citrus fruits, became a cult for many aristocrats (Crescimanno and Sottile, 2007), and the culture of citrus plants became a status symbol. In Italy, particularly during the Medicean period, this phase of "citrusmania" that gripped Europe (Wearn and Mabberley, 2016) is well documented by the huge variety of Citrus species depicted in numerous herbals, paintings and engravings (Baldini et al, 1982;Baldini, 1990). Whereas commercial plantings and, successively, significant trade of fresh fruit started in Europe after the second half of the XVIII century, the history of the specialized ornamental sector is decidedly recent.…”
Section: Introductionmentioning
confidence: 99%